Impact of Inland Tax Revenue and Import-Based Tax on GDP - Singh, Prem Bahadur (The Management Review, 2025)
This study explores the impact of inland tax revenue and import-based tax on Nepal’s GDP, focusing on the relationship between fiscal policy and economic growth. Inland tax revenue includes income tax, value-added tax (VAT), and excise duty, reflecting the country’s domestic revenue generation. In contrast, import-based tax, mainly customs duties, highlights Nepal’s reliance on foreign trade for government income. Using data from 2018 to 2023, the study applies econometric methods to assess the connection between these tax types and GDP. The results show a positive correlation between both inland and import-based taxes with GDP, indicating that improved tax collection and effective trade management contribute significantly to national economic performance. However, the study also emphasizes the importance of balanced fiscal strategies avoiding overdependence on any single revenue source. Strengthening inland tax systems while maintaining efficient trade policies is essential for long-term stability and growth. These findings offer valuable insights for policymakers aiming to optimize tax structures and support Nepal’s sustainable economic development.